Viabilidad de establecer una empresa de recolección de aceites vegetales usados a través de la metodología de economía circular en el barrio Ciudad Modelo de Santiago de Cali - Juan José Coronel Delgado; Gustavo Diaz Portillo (Universidad Antonio Nariño, 2024)
Currently, the proper management of used cooking oil waste represents an environmental and health challenge in many cities, including Cali. The inappropriate discharge of This oil in disuse can cause blockages in sewage systems, damage to the flora, water tributaries, contribute to soil pollution. Furthermore, the lack of a Proper disposal can lead to the proliferation of pests and diseases (District Secretary of Environment, 2019). Data taken from the Bogotá environmental observatory “indicate that only one liter of used oil can contaminate around 40,000 liters of water, the equivalent of annual water consumption of a person at home, as it contains approximately 5,000 times more polluting load than the wastewater that circulates through sewers and networks. sanitation.